'n Strategiese ontleding van die konflik in die benede Umzimkulu-gebied van KwaZulu-Natal (2012)
D.Litt. et Phil. === The opponents of the White minority government in South Africa succeeded in 1994, by means of the electorial process, to obtain the political power in the country. These opponents of the previous government were, and still are, a composition of members from the total demographic spectrum of South Africa's population. The composition of the Bantu population in KwaZulu-Natal was traditionally family clusters of the Nguni. Conflict occurring in KwaZulu-Natal may, with reference to the past up to the recent present, be categorised as follows: Along intra-ethnic lines - the Zulu against Zulu-related family clusters. The same concerning the Xhosa. Along inter-ethnic lines - the Zulu against the Xhosa, and later the Bantu against the Whites. Along intra- and inter-ethnic lines within the Nguni. Reference is made on the one hand to the conflict between the traditionalists and modernists within the Zulu and Xhosa peoples, and on the other hand to the conflict between the Zulu and Xhosa peoples. Given the focus of this study the inherent present conflict in KwaZulu-Natal will be addressed, and then with specific emphasis on the occurrence of conflict in the geographic and demographic contact zone, viz the lower Umzimkulu Area, where the Zulu and Xhosa peoples merge. Since the dawn of South Africa's history, KwaZulu-Natal may be regarded as the territory where geographic expansionist ideals were, by means of conflict, brought to fruition. Historically, conflict situations were initiated from the Ulundi area and these conflicts gave rise to bloody "war situations." The (strategic) aim of the (tactical) offences was already then the realisation of a (geopolitical) idea of expansion.